Detoxification of ashes from a fluidized bed waste incinerator. (September 2015) - Yu, Jie; Qiao, Yu; Sun, Lushi; Jin, Limei; Wang, Wenxia; Ma, Chuan
Highlights: Bottom and fly ashes were subject to TCLP test. Leachates of finer bottom ash and fly ash may exceed the regulatory limit. Thermal treatment of fly ash for removal of heavy metals were carried out. Almost all Cd, Pb and more than 90% of Cu and 95% of Zn could be removed. A maximum 20% of Cr was removed due to formation of stable Cr compounds. Abstract: This paper was to test and control the toxicity of bottom and fly ashes from a circulated fluidized bed (CFB) incinerator. Bottom and fly ashes were firstly subject to TCLP test. Even though leachates of most particle size of bottom ash were below regulatory limit, the leachates of finer bottom ash may exceed the regulatory limit. Therefore, finer bottom ash should be separated and treated before landfilled directly or used as cement replacement. Due to high amounts of leached heavy metals, thermal treatment of fly ash was carried out to remove heavy metals. The influence of temperature, residence time, metal chloride and gas velocity were studied. In all conditions, Cd can be well removed. Pb can be almost completely removed with MgCl2 addition at 1000 °C in 1 h. The removal of Zn and Cu was accelerated significantly by MgCl2 and higher temperature separately. At optimum conditions, more than 90% of Cu and 95% of Zn could be removed, while a maximum 20% of Cr was removed due to the existence or formation of CaCr2 O4, MgCr2 O4 and K2 Cr2 O4 in raw or treated fly ashes.